2012
DOI: 10.1063/1.3687233
|View full text |Cite
|
Sign up to set email alerts
|

Triboelectric charging of insulating polymers–some new perspectives

Abstract: A nanowire based triboelectric nanogenerator for harvesting water wave energy and its applications APL Materials 5, 074104 (2017) Tribolectric charging results from contact between surfaces, but precisely what is meant by each is not defined or understood, as they relate to charging. The recent microscopic evidence that contact charging can result from material transfer provides incentive to examine how contact charging is affected by these two factors. It is suggested that vigorous rubbing or pressing of two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 107 publications
(65 citation statements)
references
References 54 publications
0
64
0
Order By: Relevance
“…The intensive research has cast light on some triumphing trend explanation for the above triboelectric series. It has been confirmed that polymers having strong tendencies to charge positively have high dielectric constants, and are highly polar and hydrophilic [29]. For example, it is found that polymers with oxygen functional groups (more polar) will be charged more positively than those with nitrogen functional groups [36].…”
Section: Triboelectric Seriesmentioning
confidence: 93%
See 4 more Smart Citations
“…The intensive research has cast light on some triumphing trend explanation for the above triboelectric series. It has been confirmed that polymers having strong tendencies to charge positively have high dielectric constants, and are highly polar and hydrophilic [29]. For example, it is found that polymers with oxygen functional groups (more polar) will be charged more positively than those with nitrogen functional groups [36].…”
Section: Triboelectric Seriesmentioning
confidence: 93%
“…This is mainly because there may exist charge backflow when the contact surfaces are dynamically moving farther or closer, and this is a natural process if the capacitive configuration shown in Fig. 1 is considered [29]. Second, the driving force of the tribo-contacts would not completely contribute to the final surface charge density, as triboluminescence may play a role and consume some of the energy [6,12].…”
Section: Surface Charge Densitymentioning
confidence: 99%
See 3 more Smart Citations